THE EFFECT OF 5E CYCLE LEARNING MODEL ON CRITICAL THINKING SKILLS IN NATURAL SCIENCE LEARNING - Lilis Oktavia; Ahmad Muhlisin; Nuryunita Dewantari (Universitas Islam Negeri Sumatera Utara, 2022)
This study aims to determine the effect of the 5E learning cycle model on critical thinking skills in the theme of my environment being polluted at SMP Negeri 1 Candimulyo. The form of the research design used is the nonequivalent control group design. The population in this study was all seventh-grade students at SMP Negeri 1 Candimulyo while the samples used were class VII C as the experimental class and class VII D as the control class obtained through cluster sampling technique. The results showed that the indicator that had the highest increase was the explanation indicator with an average difference of 30,38 while the indicator that had the lowest increase was the inference indicator with an average difference of 11,53. In addition, from the data analysis conducted using the effect size test, the effect size (d) value was 1,762 with very high effect criteria. The effectiveness of the 5E Learning Cycle application in improving critical thinking skills can be further developed by implementing the model in the face-to-face learning process with appropriate time allocation in maximizing each learning stage.